Management of pyoperitonitis in primary healthcare setting: a case report - Silwal, Mahesh (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Pyoperitonitis can rapidly progress to septic shock which leads to extremely high morbidity and mortality. The current guidelines outline the core percepts of care including prompt resuscitation, appropriate antibiotics, and meticulous source control. However, the management of such cases poses one of the biggest challenges, especially in resource-limited settings. It is critical that such cases are meticulously dealt with, as the risk of sepsis and consequently septic shock and organ damage is extremely high. A comprehensive case report will be used in this article to highlight the management of pyoperitonitis in primary healthcare setup.